2021
DOI: 10.1186/s40792-021-01237-0
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer in Crohn’s disease: a series of 6 cases

Abstract: Background Colorectal cancer (CRC) is the most malignant complication in patients with Crohn’s disease (CD). We report 6 cases of CD-related CRC treated surgically at our hospital. Case presentation From 2010 to 2016, six CD patients were diagnosed with CRC. All patients were diagnosed with CD at < 25 years old, and the interval from onset of CD to diagnosis of CRC was > 10 years (range, 15–42 years) in all patients. The histological type of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…As expected, risk factors for CRC development in CD include younger age at CD diagnosis and disease duration > 10 years. While non-mucinous adenocarcinoma is still the most prevalent CRC identified in patients with Crohn’s disease, there is a higher prevalence of the mucinous subtype in patients with Crohn's disease as compared to the general population [ 8 ] Compared to non-mucinous adenocarcinoma, patients with the mucinous subtype are usually diagnosed at a more advanced stage and have a poorer response to chemotherapies. A recent population-based study reported an approximately 93% 5-year survival rate for patients with localized disease [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…As expected, risk factors for CRC development in CD include younger age at CD diagnosis and disease duration > 10 years. While non-mucinous adenocarcinoma is still the most prevalent CRC identified in patients with Crohn’s disease, there is a higher prevalence of the mucinous subtype in patients with Crohn's disease as compared to the general population [ 8 ] Compared to non-mucinous adenocarcinoma, patients with the mucinous subtype are usually diagnosed at a more advanced stage and have a poorer response to chemotherapies. A recent population-based study reported an approximately 93% 5-year survival rate for patients with localized disease [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is the third most prevalent malignant tumor and the second most prevalent cause of cancer death in the world. Generally, CRC occurs in people older than 50 [ 1 ], more in men than in women [ 2 ], and in those who have a family history of CRC [ 3 ] as well as inflammatory bowel disease [ 4 ]. Overweight or obesity [ 5 ], low physical exercise [ 6 ], excess consumption of red meat and processed meat, diets low in fiber, calcium, milk, and whole grains [ 7 ], smoking [ 8 ], and alcohol use [ 9 ] are risk factors for this pathology.…”
Section: Introductionmentioning
confidence: 99%